Gadolinium-based relative contrast enhancement in primary sclerosing cholangitis: additional benefit for clinicians?. Issue 7 (July 2018) - Keller, S.; Venkatesh, S.K.; Avanesov, M.; Weinrich, J.M.; Zenouzi, R.; Schramm, C.; Adam, G.; Yamamura, J.
Abstract : Aim: To evaluate the benefit of extracellular gadolinium-based contrast agent (GBCA) enhanced magnetic resonance imaging (MRI) in addition to conventional non-enhanced T2-weighted imaging (WI) for quantification of inflammatory or fibrotic alterations in the liver parenchyma of patients with primary sclerosing cholangitis (PSC). Material and methods: MRI (3 T) examinations were reviewed retrospectively by two radiologists in 27 PSC patients (age 42.9±15.6 years), and 19 controls. Regions of interest (ROIs) were drawn onto T2 hyperintense and T2 isointense areas and copied to section position matched non-enhanced and delayed-phase contrast-enhanced T1WI. Signal intensities (SI) obtained from ROIs of the multiphase T1WI were used to calculate relative liver enhancement (RLE). The interobserver agreement of RLE and quantified T2 signal was calculated using Bland–Altman analysis. RLE assessed for both T2 hyperintense (RLEhyper ) and T2 isointense (RLEiso ) areas were compared in patients and controls (RLEhealthy ). Results: The interobserver agreement of RLE in affected hyperintense areas (bias −0.77, limits of agreement −51.7 to 50.1) was superior to the quantification of T2 signal only in these areas (bias −3.35, limits of agreement −162.4 to 155.7). The RLEhyper (86.2±9.7%) was higher than the RLEiso (59.8±6.2%, p =0.03) and the RLEhealthy (53.2±2.7%, p =0.002). The mean RLEiso was not significantly different from the RLEhealthy ( p =0.3). Conclusion: The extracellular gadolinium-based RLE of T2 hyperintense areas could be a useful add-on for routine follow up MRI in the detection of early inflammatory changes, possibly preceding formation of fibrotic scarring in PSC patients, if validated in larger cohorts. Highlights: The RLE and T2 signal intensity are typically shifted in primary sclerosing cholangitis. Hyperintensity on T2 weighted imaging is connected to gadolinium-based contrast enhancement. The relative liver enhancement (RLE) provides a quantitative measure of the liver parenchyma.